Histological and multi-biomarker analyses in Limanda limanda collected from shipwrecks in the North Sea to assess the biological effects of old World War munitions - Romina Marietta Schuster; Franziska Isabelle Binder; Maarten De Rijcke; Sven Van Haelst; Katrine Juul Andresen; Matthias Brenner (PANGAEA, 2025)
This dataset documents field investigations on the biological effects of legacy World War I munitions on marine organisms, with a focus on shipwreck sites in the North Sea. Three historically well-documented wrecks were selected: the light cruiser SMS Mainz, the minelayer SMS Ariadne, and the submarine UC30. These wrecks were chosen based on detailed archival information regarding their sinking circumstances and cargo, their unambiguous identification, and their accessibility for scientific diving operations. As a munition-free control, a reference area outside known wreck fields was sampled (Naturschutzgebiet Borkum Riffgrund). The flatfish Limanda limanda (dab) was selected as a sentinel species. Sampling was conducted during several cruises with the research vessel Heincke (HE 573, April 2021 – SMS Mainz; HE 596, April 2022 – UC30 and SMS Ariadne; HE 607, September 2022 – UC30; HE 613, February 2023 – SMS Ariadne) and with the Uthörn (May 2022 – reference site). Fish were caught using bottom trawls deployed as close as possible to the wreck structures. Captured fish were transferred to seawater tanks prior to dissection. Each specimen was measured, weighed, and assessed biometrically to calculate condition factors as indicators of general health. Subsequent processing included macroscopic examination of livers for pathological alterations (e.g., fatty liver, nodules, bile stasis, tumor formation). Liver tissue was partitioned for histological analysis (H&E staining after methacrylate embedding), histochemical biomarker assays (lipofuscin accumulation, neutral lipids, lysosomal membrane stability), and biochemical measurements. Enzyme activities of catalase (CAT) and glutathione S-transferase (GST) were quantified in liver and muscle homogenates using spectrophotometric assays and normalized to protein content. Both otoliths were extracted for age determination, dried, embedded in resin, and microscopically examined under variable light intensities to identify annual growth rings. The resulting dataset integrates biometric data, liver pathology, histological and histochemical biomarkers, enzyme activity profiles, and otolith-based age determinations from dabs collected at munition-affected shipwrecks and a reference site. It provides a standardized and comprehensive resource to evaluate the potential toxicological effects of World War I munitions on marine fish populations in the North Sea.